"Duplication" of aortic cusp. New M-mode echocardiographic sign of intimal tear in aortic dissection. Issue 2 (February 1982) - Cohen, I S; Wharton, T P
Abstract : M-mode and two-dimensional echocardiograms were obtained in a patient with acute dissecting aneurysm of the ascending aorta. The M-mode echocardiogram disclosed apparent "duplication" of the non-coronary aortic cusp. Two-dimensional echocardiograms showed this finding to be the result of the motion of a flap of torn aortic intima. This new M-mode finding appears to be a highly specific echocardiographic sign for aortic dissection.